KONSEP KECERDASAN SPRITUAL PESERTA DIDIK MENURUT AL-QUR’AN DAN HADIST - Arben Arben; Wahidah Fitriani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
This article explores the concept of students' spiritual intelligence according to the Qur'an and Hadith. Spiritual intelligence refers to the ability to solve problems based on spiritual values, which are often reflected in wisdom and broad understanding. It is hoped that this article can provide a positive contribution to readers regarding the concept of students' spiritual intelligence through the Qur'an and Hadith. This research uses a systematic literature review. Literature research is a theoretical study, references, and other scientific literature related to the culture, values, and norms that develop in the social situation being studied. Data collection for the literature review was carried out through a literature review of relevant reference sources from books and journals for analysis and classification. In this study, the researcher used a qualitative descriptive analysis technique. The research analysis was directed at finding knowledge or theories related to previous research through books, national journals, and international journals. This article further emphasizes the concept of students' spiritual intelligence according to the Qur'an and Hadith is very important for creating a whole individual and aligning their actions with Divine guidance. Spiritual intelligence provides students with inner peace, wisdom, and the ability to navigate life's challenges. This finding concludes that according to the Qur'an and Hadith, students' spiritual intelligence is a secret to success towards personal actions that are meaningful and value-based.